Design standard for steel construction (Japan : The Architectural Institute of Japan, 1979)
Research completed since the last revision of the AIJ Design Standard for steel structures in 1959 accounts for most of the changes in the present revision.
General -- Drawing practice -- Calculation of loads and stresses -- Materials -- Allowable stresses -- Combined stress -- Members and connections subject to repeated variation of stress -- Width-ti-thickness ratio of plate elements -- Beams and girders -- Deflection -- Compression members and columns -- Tension members -- Net sections -- Connections -- Rivets, bolts and high-strength bolts -- Welds -- Column bases.
Keywords: BUILDING, IRON AND STEEL